Cerebellar BDNF Promotes Exploration and Seeking for Novelty - Laricchiuta, Daniela; Andolina, Diego; Angelucci, Francesco; Gelfo, Francesca; Berretta, Erica; Puglisi-Allegra, Stefano; Petrosini, Laura (International journal of neuropsychopharmacology, 2018)
Background: Approach system considered a motivational system that activates reward-seeking behavior is associated with exploration/impulsivity, whereas avoidance system considered an attentional system that promotes inhibition of appetitive responses is associated with active overt withdrawal. Approach and avoidance dispositions are modulated by distinct neurochemical profiles and synaptic patterns. However, the precise working of neurons and trafficking of molecules in the brain activity predisposing to approach and avoidance are yet unclear. Methods: In 3 phenotypes of inbred mice, avoiding, balancing, and approaching mice, selected by using the Approach/Avoidance Y-maze, we analyzed endogenous brain levels of brain derived neurotrophic factor, one of the main secretory proteins with pleiotropic action. To verify the effects of the acute increase of brain derived neurotrophic factor, balancing and avoiding mice were bilaterally brain derived neurotrophic factor-infused in the cortical cerebellar regions. Results: Approaching animals showed high levels of explorative behavior and response to novelty and exhibited higher brain derived neurotrophic factor levels in the cerebellar structures in comparison to the other 2 phenotypes of mice. Interestingly, brain derived neurotrophic factor-infused balancing and avoiding mice significantly increased their explorative behavior and response to novelty. Conclusions: Cerebellar brain derived neurotrophic factor may play a role in explorative and novelty-seeking responses that sustain the approach predisposition.
Keywords: Exploratory Behavior; Mice; Animals; Brain-Derived Neurotrophic Factor; Mice, Inbred C57BL; Male; mozek; Brain; chování zvířat; mužské pohlaví; myši; pátrací chování; zvířata; Behavior, Animal; myši inbrední C57BL; mozkový neurotrofický faktor